x = –6
Solution:
Given expression is
.
Step 1: Isolate the radical by subtracting 5 from both sides of the equation.
![\Rightarrow\sqrt[3]{x-2}+5-5=3-5](https://tex.z-dn.net/?f=%5CRightarrow%5Csqrt%5B3%5D%7Bx-2%7D%2B5-5%3D3-5)
![\Rightarrow\sqrt[3]{x-2}=-2](https://tex.z-dn.net/?f=%5CRightarrow%5Csqrt%5B3%5D%7Bx-2%7D%3D-2)
Step 2: Cube both sides of the equation to remove the cube root.
![\Rightarrow(\sqrt[3]{x-2})^3=(-2)^3](https://tex.z-dn.net/?f=%5CRightarrow%28%5Csqrt%5B3%5D%7Bx-2%7D%29%5E3%3D%28-2%29%5E3)
Cube and cube root get canceled in left side of the equation.
![\Rightarrow\ x-2=-8](https://tex.z-dn.net/?f=%5CRightarrow%5C%20x-2%3D-8)
Step 3: To solve for x.
Add 2 on both sides of the equation.
![\Rightarrow\ x-2+2=-8+2](https://tex.z-dn.net/?f=%5CRightarrow%5C%20x-2%2B2%3D-8%2B2)
![\Rightarrow\ x=-6](https://tex.z-dn.net/?f=%5CRightarrow%5C%20x%3D-6)
Hence the solution is x = –6.
Answer:
x=135
Step-by-step explanation:
We know that sin(270) = -1/2
So 2x = 270
x = 135
We need more info like a) this b) or this stuff like that
Answer:
3.36
Step-by-step explanation:
.20 x 2.80 = .56
2.80 + .56 = 3.36
Answer: 6 - k
Step-by-step explanation:
Difference means subtraction